2009
DOI: 10.1016/j.juro.2008.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Early Recovery of Urinary Continence After Radical Prostatectomy Using Early Pelvic Floor Electrical Stimulation and Biofeedback Associated Treatment

Abstract: Early, noninvasive physical treatment with biofeedback and pelvic floor electrical stimulation has a significant positive impact on the early recovery of urinary continence after radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
3
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 22 publications
1
90
3
12
Order By: Relevance
“…Although the severity of urinary incontinence often decreases with time after RP [6][7][8], previous studies have demonstrated that 8% to 87% of patients still experience urinary incontinence at six months and 5% to 44.5% remain incontinent at one to two years after surgery [7][8][9][10][11][12]. Moreover, up to 50% of patients report some degree of incontinence two years after RP [3], even after pelvic fl oor muscle exercise intervention.…”
Section: Urinary Incontinencementioning
confidence: 99%
“…Although the severity of urinary incontinence often decreases with time after RP [6][7][8], previous studies have demonstrated that 8% to 87% of patients still experience urinary incontinence at six months and 5% to 44.5% remain incontinent at one to two years after surgery [7][8][9][10][11][12]. Moreover, up to 50% of patients report some degree of incontinence two years after RP [3], even after pelvic fl oor muscle exercise intervention.…”
Section: Urinary Incontinencementioning
confidence: 99%
“…In the long term results of researches has a significant proportion of patients but they haven't demonstrated symptoms of continence. (Ribeiro et al 2010, Mariotti et al 2009). Patients must choose comfortable clothes and must be relax before exercise.…”
Section: Pelvic Floor Exercise (Level Of Evidence 1; Grade Of Recommementioning
confidence: 99%
“…Predictive factors for postoperative and postradiotherapy LUTS are summarised in Table 2 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26. Known risk factors such as prior transurethral resection have been well evidenced, but probable risk factors such as central nervous system damage and/or cognitive impairment is less well defined in the cancer population but is essential in the assessment of LUTS.…”
Section: Introductionmentioning
confidence: 99%